New imidazole-2-thiones linked to acenaphythylenone as dual DNA intercalators and topoisomerase II inhibitors: structural optimization, docking, and apoptosis studies - Asmaa H. Mohamed; Mohammed B. Alshammari; Ashraf A. Aly; Kamal U. Sadek; Akil Ahmad; Eman A. Aziz; Amira F. El-Yazbi; Eman J. El-Agroudy; Marwa E. Abdelaziz (Taylor & Francis Group, 2024)
AbstractIn this article, a new series of 2-((3,5-disubstituted-2-thioxo-imidazol-1-yl)imino)acenaphthylen-1(2H)-ones were synthesized. Imidazole-2-thione with acenaphthylen-one gave a hybrid scaffold that integrated key structural elements essential for DNA damage via direct DNA intercalation and inhibition of the topoisomerase II enzyme. All the synthesized compounds were screened to detect their DNA damage using a terbium fluorescent probe. Results demonstrated that 4-phenyl-imidazoles 5b and 5e in addition to 4-(4-chlorophenyl)imidazoles 5h and 5j would induce detectable potent damage in ctDNA. The four most potent compounds as DNA intercalators were further evaluated for their antiproliferative activity against HepG2, MCF-7 and HCT-116 utilizing the MTT assay. The highest anticancer activity was recorded with compounds 5b and 5h against the breast cancer cell line MCF-7 which were 1.5- and 3- folds more active than doxorubicin, respectively. Therefore, imidazole-2-thione tethered acenaphthylenone derivatives can be considered as promising scaffold for the development of effective dual DNA intercalators and topoisomerase II inhibitors.